Characteristics of Authentic Leadership and Women's Leadership in the Digital Era - Gilang Aulia Prasetya; Hasyim Asy’ari; Hilmiyatul Latifah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research aims to analyze the relationship between Authentic Leadership Characteristics and Women's Leadership in the Digital Era. This approach uses descriptive qualitative with the aim of producing descriptive data in the form of written or spoken words from individuals and observed behavior. Data collection is carried out from interview activities, field notes, recordings, and so on. Female leaders who adopt an authentic leadership style are usually able to demonstrate integrity and openness, thereby building trust and cooperation with subordinates and colleagues. This leadership style also provides an opportunity for women to show that they can lead effectively, without having to imitate the more authoritarian or hierarchical leadership styles of men. There are five characteristics generally possessed by women who lead: 1) Persuasion skills. 2) Their feminine nature, and empathy remain; proves criticism is inappropriate, 3) Team enthusiasm, brilliant female leaders usually apply a holistic leadership approach when facing challenges and making decisions. 4) A leader, an extraordinary female leader generally has a strong attraction, just like men. 5) Dare to take risks, no longer in a comfort zone, female leaders naturally dare to challenge boundaries and take risks, similar to men while still paying attention to details.